PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN - SUKRISPIYANTO -; ANGGA SUWIGNYO (STIE Indonesia Malang, 2017)
This research aims to analyze the influence of leadership styles and the work environment onperformance of employees. This research type is explanatory research. Based on the results ofthe examination of the 40 respondents, it can be concluded that there is a leadership styleand influence of work environment on performance of employees. It can be seen from the F-value count of 62.668 with significance < 5% (0.05) of 0.000 together whereby theindependent variable (the leadership style and work environment) effect significantly to thedependent variable (performance). The t-test results obtained from that leadership style andwork environment are partial positive and significant effect on performance of employees.Whereas the coefficient of determination R Square of 0.877 obtained, which means that87.7% change dependent variable (performance of employees) are capable of independentvariable explained by the (leadership style and work environment). The rest amounted to12.3% is explained by other variables outside of the variables used.Keywords: leadership styles, Employee Performance.